The Role of Antioxidant Therapy in the Management of Type 2 Diabetes Mellitus: A Literature Review - Astini, Dewa Ayu Agung Alit Suka; Yasa, I Wayan Putu Sutirta; Jawi, I Made; Wande, I Nyoman (Review of Primary Care Practice and Education, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a metabolic disease and has become a global problem due to the rapid increase in the number of cases. This disease is characterized by chronic hyperglycemia caused by insulin resistance and pancreatic beta cell dysfunction. The occurrence of oxidative stress is known to play a central role in the development of T2DM complications, through increased reactive oxygen species (ROS) that worsen insulin resistance, worsen beta cell function, and trigger complications such as cardiovascular complications, nephropathy, and neuropathy. Objectives: This literature review aims to evaluate the scientific evidence supporting the use of antioxidant therapy as an additional approach in the management of T2DM, focusing on the effectiveness and mechanism of action of antioxidant compounds on glycemic parameters, oxidative stress, and diabetes complications. Methods: A literature search was conducted through databases on ScienceDirect, PubMed, and Google Scholar, with the keywords "antioxidant therapy", "type 2 diabetes mellitus", "oxidative stress", and "diabetes management". The selected articles included in vitro, in vivo studies, and clinical trials published in the period 2013-2023. Literature review focused on the biochemical mechanisms of antioxidant compounds and clinical outcomes related to glycemic parameters and diabetes complications. The literature extraction process was carried out from January to March 2024. Results: Supplementation of vitamin D, vitamin E, vitamin C, polyphenols, saponins, and flavonoids has been proven to reduce blood glucose levels and increase insulin sensitivity in type 2 diabetes mellitus. The mechanism involves increasing antioxidant activity, regulating glucose homeostasis, as well as modulating signaling pathways such as AMPK, PPAR, and GLUT4. Conclusions: This bioactive compound has potential as an adjunct therapy in the management of type 2 diabetes mellitus by targeting oxidative stress and insulin resistance. Further research is needed to determine optimal dosage and long-term effectiveness.